(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This research endeavors to tackle the problem of synthetically manufactured fertilizers and escalating prices of cooking gas that pose a challenge to socioeconomically disadvantaged communities, specifically in Perak, Malaysia. The proposed solution is the implementation of a portable bio-digester, aimed at producing biogas and bio fertilizer as sustainable alternatives to traditional cooking fuel and commercial fertilizers, respectively. The investigation encompasses the design, fabrication and optimization of the bio-digester’s structural design and analysis. Additionally, it examines economic viability, structural integrity, and considerations related to ergonomics of the portable bio-digester. The research study is in accordance with the seventh Sustainable Development Goal (SDG) of the United Nations which aims to guarantee universal access to affordable, reliable, sustainable, and modern energy. The outcomes of this research will provide a comprehensive evaluation of the feasibility and viability of using portable bio-digesters with various types of feeds to generate sustainable cooking fuel and bio-fertilizer respectively.